Structural and Biophysical Characterization of Purified Recombinant Arabidopsis thaliana's Alternative Oxidase 1A (rAtAOX1A): Interaction With Inhibitor(s) and Activator - Sankar, Tadiboina Veera; Saharay, Moumita; Santhosh, Dharawath; Vishwakarma, Abhaypratap; Padmasree, Kollipara (Frontiers in Plant Science, 2022)
In higher plants, alternative oxidase (AOX) participates in a cyanide resistant, non-proton motive electron transport pathway of mitochondria, diverging from ubiquinone pool. The physiological significance of AOX in biotic/abiotic stress tolerance is well documented. However, its structural and biophysical properties are poorly understood as its crystal structure is not yet revealed in plants. Also, most of the AOX purification processes resulted in a low yield/inactive/unstable form of native AOX protein. The present study aims to characterize the purified rAtAOX1A protein and its interaction with inhibitors such as salicyl hydroxamic acid (SHAM) and n-propyl gallate (n-PG) as well as pyruvate (activator) using biophysical/in-silico studies. The rAtAOX1A expressed in E. coli BL21(DE3) cells was functionally characterized by monitoring the respiratory and growth sensitivity of E. coli/pAtAOX1A and E. coli/pET28a to classical mitochondrial electron transport chain (mETC) inhibitors. The rAtAOX1A, which is purified through affinity chromatography and confirmed by western blotting and MALDI-TOF-TOF studies, showed an oxygen uptake activity of 3.86 µmol min-1 mg-1 protein, which is acceptable in non-thermogenic plants. Circular dichroism (CD) studies of purified rAtAOX1A revealed that >50% of the protein content was α-helical and retained its helical absorbance signal (ellipticity) at a wide range of temperature and pH conditions. Further, interaction with SHAM, n-PG or pyruvate caused significant changes in its secondary structural elements while retaining its ellipticity. Surface plasmon resonance (SPR) studies revealed that both SHAM and n-PG bind reversibly to rAtAOX1A, while docking studies revealed that both of them bind to the same hydrophobic groove (Met191, Val192, Met195, Leu196, Phe251 and Phe255) as that of Duroquinone (DQ), in the AtAOX1A. In contrast, pyruvate binds to a pocket consisting of Cys II (Arg174, Tyr175, Gly176, Cys177 Val232, Ala233, Asn294 and Leu313). Further, the mutational docking studies suggest that (i) the Met195 and Phe255 of AtAOX1A are the potential candidates to bind the inhibitor. Hence, this binding pocket could be a ‘potential gateway’ for the oxidation-reduction process in AtAOX1A, and (ii) Arg174, Gly176 and Cys177 play an important role in binding to the organic acids like pyruvate.